2012
DOI: 10.1016/j.bbadis.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in Down syndrome

Abstract: Individuals with Down syndrome (DS) have high levels of oxidative stress throughout the lifespan. Mouse models of DS share some structural and functional abnormalities that parallel findings seen in the human phenotype. Several of the mouse models show evidence of cellular oxidative stress and have provided a platform for antioxidant intervention. Genes that are overexpressed on chromosome 21 are associated with oxidative stress and neuronal apoptosis. The lack of balance in the metabolism of free radicals gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 109 publications
2
65
0
Order By: Relevance
“…Other authors suggested that controlled supplementation with antioxidant, physical activity and regular exercise could be used to improve the cognitive functions . Prophylactic trial may hold more encouragement in DS and early intervention with strategically developed antioxidants may positively impact intellectual functioning decades before dementia sets in …”
Section: Discussionmentioning
confidence: 99%
“…Other authors suggested that controlled supplementation with antioxidant, physical activity and regular exercise could be used to improve the cognitive functions . Prophylactic trial may hold more encouragement in DS and early intervention with strategically developed antioxidants may positively impact intellectual functioning decades before dementia sets in …”
Section: Discussionmentioning
confidence: 99%
“…OS represents an imbalance between the production of ROS and the efficiency of antioxidant systems - antioxidant compounds and antioxidant enzymes - to detoxify the reactive intermediates or to repair the oxidative damage [18, 19]. High levels of OS-induced by-products have been detected in brain tissue from DS [19, 20].…”
Section: Increased Oxidative Stress In Ds Contributes To Developmementioning
confidence: 99%
“…There is consequently a gene dosage effect in DS leading to $50% greater levels of SOD-1 and elevated endogenous production of hydrogen peroxide (H 2 O 2 ), and potentially of hydroxyl radical ( OH) (Garlet et al, 2013;Lott, 2012), which is the most reactive and deleterious ROS inducing damage in proteins, lipids and DNA (Halliwell & Gutteridge, 2007).…”
mentioning
confidence: 99%